Plasma Galectin-3 Biomarkers in Chronic Kidney Disease - Annesa Fadella; Harnavi Harun; Drajad Priyono; Deka Viotra (International Journal Labs, 2023)
Assessment of renal function is based on determination of serum creatinine and creatinine-based equations to assess GFR. However, this marker is not perfect or accurate, especially for longitudinal monitoring of kidney function in Chronic Kidney Disease (CKD patients). Decreased kidney function can be slowed or even anticipated with early detection, so as to avoid secondary complications. So it is important to find new biomarkers that can identify individuals at risk as early as possible. Plasma galectin-3 is a ?-galactoside-binding lectin expressed in monocytes, which plays an important role in inflammation, immunity, cancer, and is involved in the pathogenesis of atherosclerosis, diabetes, renal fibrosis and asthma. Higher galectin-3 levels were associated with reduced eGFR in a cross-sectional study. Galectin-3 is essential in various biological activities including cell growth, cell proliferation, differentiation, apoptosis, pre-mRNA splicing, transformation, angiogenesis, inflammation, fibrosis, fibrogenesis and host defense. Galectin-3 is a stable biomarker and is not associated with age, body mass index or sex. Galectin-3 is also useful for detecting the early stages of some diseases. Galectin-3 shows no circadian variation and increases slightly after exercise, returning to normal levels after 1-3 hours. Higher concentrations of galectin-3 may be associated with CKD development, indicating the potential for new mechanisms related to galectin-3 expression that may contribute to CKD development. Galectin-3 has also been reported to play an important role in renal interstitial fibrosis. Thus, galectin-3 inhibition may be a promising therapeutic strategy to prevent kidney disease progression.